2016
DOI: 10.1016/j.pmrj.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Value of Assessing Lumbar Posteroanterior Segmental Stiffness: A Narrative Review of Manual and Instrumented Methods

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 96 publications
(194 reference statements)
2
39
0
Order By: Relevance
“…As distinct from reliability, perhaps the clearest summary of the clinical relevance of the relationship between PIVM testing and clinical outcomes is found in a recent review relating to the lumbar spine [53], which concluded amongst other things that 1) Patients with low back pain may have increased PA stiffness, 2) PA stiffness decreases as symptoms improve, at least in some patients, 3) Patients…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As distinct from reliability, perhaps the clearest summary of the clinical relevance of the relationship between PIVM testing and clinical outcomes is found in a recent review relating to the lumbar spine [53], which concluded amongst other things that 1) Patients with low back pain may have increased PA stiffness, 2) PA stiffness decreases as symptoms improve, at least in some patients, 3) Patients…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies that measured and compared PA movements in clinically relevant settings, focused on the stiffness near the end of range. A review of previous studies [53] indicated that a variety of methods and rationale were used to reduce the data in the curves to one or two values that were thought to represent the overall mobility. Although it has been clearly demonstrated that no region of the F-D curves of PA movements are linear [55], these studies calculated stiffness as a linear approximation of a portion of the F-D curves.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, a change in spinal stiffness does not necessarily imply an increase in spinal mobility. Indeed, spinal stiffness represents the stiffness of underlying tissues throughout the application of load or, in other words, the tissue dynamics in response to the application of load [34,35]. It is, therefore, possible to observe a change in the spinal stiffness without any change in spine mobility.…”
Section: Increased Mobilitymentioning
confidence: 99%
“…Manual assessment methods to localize tender points in soft tissues, perform pain provocation tests and joint motion palpation, determine tissue tone and use of "low-tech" device assessments such as goniometry or inclinometry designed to quantify mobility can be combined with visual inspection of posture and basic movements (Lemeunier et al, 2018). Several functional assessment protocols have been proposed, and despite reliability and validity issues regarding subjective manual (Koppenhaver et al, 2014;Telli et al, 2018;van Trijffel et al, 2014;Wong and Kawchuk, 2017) and/or visual evaluation methodologies (Elgueta-Cancino et al, 2014;Lemeunier et al, 2018;O'Leary et al, 2015;Rathinam et al, 2014;Roussel et al, 2007), clinicians tend to utilize them routinely because sophisticated laboratory tests to examine motor behavior have limited utility in clinical practice (Elgueta-Cancino et al, 2014). This suggests that practicality remains a priority as practitioners require clear and simple evaluation protocols using sheets to record and monitor their patients over time during clinical interventional management.…”
Section: Introductionmentioning
confidence: 99%